Diversity of narrative context disrupts the early stage of learning the meanings of novel words - Hulme, RC; Begum, A; Nation, K; Rodd, JM (Springer, 2023)
High quality lexical representations develop through repeated exposures to words in different contexts. This preregistered experiment investigated how diversity of narrative context affects the earliest stages of word learning via reading. Adults (N = 100) learned invented meanings for eight pseudowords, which each occurred in five written paragraphs either within a single coherent narrative context or five different narrative contexts. The words’ semantic features were controlled across conditions to avoid influences from polysemy (lexical ambiguity). Posttests included graded measures of word-form recall (spelling accuracy) and recognition (multiple choice), and word-meaning recall (number of semantic features). Diversity of narrative context did not affect word-form learning, but more semantic features were correctly recalled for words trained in a single context. These findings indicate that learning the meanings of novel words is initially boosted by anchoring them to a single coherent narrative discourse.